Exploring the influence of gut microbiota metabolites on vitiligo through the gut-skin axis - Yuan, Chuanjian; Liu, Lyuye; Zeng, Duorong; Yuan, Jinxiang; Guo, Liyuan; Zhang, Junling (Frontiers in Microbiology, 2025)
Vitiligo is an autoimmune skin disease with a complex pathogenesis closely linked to immune imbalance and oxidative stress. Currently, comprehensive curative treatments and effective relapse prevention strategies are lacking. Recently, the “gut-skin axis” hypothesis has offered new insights into the pathological mechanisms of vitiligo. Studies indicate that gut microbiota and their metabolic products significantly affect disease progression by regulating immune homeostasis and inflammatory responses in the host. This review systematically examines the effects of short-chain fatty acids, secondary bile acids, and tryptophan metabolites on the human immune system and the inflammatory milieu, and their direct impact on melanocytes. Furthermore, considering the reduced diversity of gut microbiota in individuals with vitiligo, this article also evaluates methods including probiotic intervention, the Mediterranean diet, and fecal microbiota transplantation, which may emerge as potential therapeutic strategies for vitiligo by restoring microbiota balance. Future multidimensional therapeutic strategies that target gut microbiota metabolites show promise for pioneering innovative approaches in vitiligo management.